Algorithm of implementation of the project management system into the state bodies of the Republic of Kazakhstan - Oinarov, A.R.; Dushabaev, D.Sh.; Kartov, A.E. (BUKETOV BUSINESS REVIEW, 2017)
The increasing pressure of external factors that reduce commodity prices, the preservation of sanctions between the countries of the West and Russia, leads to negative consequences for the socio-economic development of Kazakhstan. In such crisis conditions, the urgency of rational and effective use of the funds allocated by the state for the implementation of state projects and programs is growing. Therefore, the introduction of management systems for the project activity of the Government of the Republic of Kazakhstan is proposed, since the project management system will be determined by the government's activity procedure: the system of bodies and the role structure of the project activity. This will be a new format of work for the authorities, and a kind of instruction on the effective execution of projects. And also, it will give a procedural description of the process: how to initiate projects, who and how is responsible for their implementation, who and how to control the results. Currently, work is actively being carried out to implement the project management system in the public sector of the Republic of Kazakhstan. In this article, a step-by-step introduction of the system of project activity of state bodies of the Republic of Kazakhstan is considered, its shortcomings and problems are indicated, as well as ways to solve it. The authors considered: the current legislative framework, during which gaps in the field of public administration were identified. On the basis of the analysis carried out, through an information approach, an existing model of project management elements is built that does not cover all elements of the methodology of project management of the best world practices. The authors suggest an algorithm for implementing a project management system for government agencies of the Republic of Kazakhstan.